Citizen Involvement: Fostering Alternatives and Risk Considerations on Natuna Rural Coastal Borderland - Armauliza Septiawan; Sintanigrum Sintanigrum (Universitas Muhammadiyah Gorontalo, 2018)
The rural coastal development phenomenon in Natuna Regency hasn’t shown improvement significantly, especially in potential development resources utilizing to be a strategy and performance which can reduce the development problems faced. This study aims to explore the suitability of the rural coastal development strategy with its main mission, alternative actions where are the risk considerations and also the citizen involvement on the rural coastal development strategy. This research using a qualitative approach. Hence, the research process is carried out deeply and through the data collection techniques process systematiclythrough of interviewing informants in the field, studying data and relevant information analyzing. The results explain about the Natuna rural coastal development strategy has not fully implemented the risk considerations as a main consequence to thedevelopment benefits failure activities undertaken. This finding is the lack of involvement influence for the rural coastal villagers, especially in the citizen’s idea repositioning process as an alternative forrural developing strategy implemented,thus for the development goals achieving in Natuna rural coastal.